The Development of Nonlinear Metrology Methods - Machekhin, Yu. P.; Kurskoy, Yu. S. (My University, 2015)
The article contains the results of research in a new perspective sphere of nonlinear metrology. The special measurement model and measurement results analysis model, that based on the main principles and concepts of dynamical chaos theory and fractal representations of the real systems behavior, are offered in the frame of nonlinear metrology theory. The model of human health measurement is represented here. It has the numerical portrait, entropy and time lines for evaluation of human health condition. It can be used for assess the state of human health during a treatment or an athletic training.
Keywords: nonlinear metrology; nonlinear dynamical system